Strain induced electronic and magnetic properties of 2D magnet CrI3: a DFT approach. (30th May 2019) - Mukherjee, Tista; Chowdhury, Suman; Jana, Debnarayan; Voon, L C Lew Yan
Abstract: In the post-graphene era, out of several monolayer 2D materials, Chromium triiodide ( ) has triggered an exotic platform for studying the intrinsic ferromagnetism and large anisotropy at the nanoscale regime. Apart from that, its strong spin–orbit coupling of I also plays a key role in tailoring the electronic properties. In this work, the composition of compressive and tensile strain (uniaxial as well as biaxial) upto 12% have been applied to study the variation of the electronic and magnetic properties of employing density functional theory in (LDA+ U ) exchange correlation scheme. The stability limits of the structures under the influence of strains have been carried out via the deformation potential (DP) and stress–strain relation. For compressive strains in specific directions, the down-spin band gap is seen to be decreasing steadily. The magnetic moment computed from the density of states (DOS) is enhanced significantly under the influence of compressive strain. However, it has been observed that after the application of strain in some specific crystal directions, the magnetic moment of monolayer remains almost unchanged. Thus, with the help of strain, the tunning band gap along with underlying characteristic ferromagnetism of this material can unfold a new avenue for potential usage in spintronic devices.